Key career planning competences for Chinese college students in Shanxi province: An exploratory factor analysis - Yao, Xinmeng; Tuntinakhongul, Ampapan; Sumettikoon, Piyapong (Edelweiss Applied Science and Technology, 2025)
This study aimed to identify key career planning competencies to enable Chinese college students to navigate the complexities of the modern labor market. It conducted a survey in Shanxi Province, China, to determine the essential career planning competencies for Chinese college students. A random sample of 372 teaching and administrative staff from six universities in Shanxi Province participated in the study. Fourteen career planning skills were reviewed, and data were analyzed using exploratory factor analysis. The results identified four competency dimensions, with their respective contributions as follows: Information Seeking and Decision-Making (23.186%), Goal Setting and Planning (15.399%), Interpersonal and Communication Skills (14.996%), and Self-Awareness (14.682%). Five skills were classified under Information Seeking and Decision-Making, while three skills were categorized into each of the remaining three dimensions. The findings offer a comprehensive framework of career planning competencies, which can effectively support the development of students’ skills for their future careers.